2022
DOI: 10.1007/s00784-022-04795-1
|View full text |Cite
|
Sign up to set email alerts
|

Accurate gingival recession quantification using 3D digital dental models

Abstract: Objectives To develop and validate a method for accurate quantitative assessment of gingival recessions based on superimposition of serial 3D digital models. Materials and methods Gingival recessions of mild (0.5–2 mm) and increased (3–7 mm) severity were simulated on stone casts and surface models were created. The outlines of the gingival margins of the mild (A) and severe recessions (B) were compared to the original gingival margins following 3D best fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
1
1
1
Order By: Relevance
“…Nevertheless, several more successful approaches were described in the literature in terms of digital evaluation of gingival recession [16]. Moreover, the digital approach used for the measurements of gingival recession was found to be more reproducible and valid compared to the conventional clinical examination [14][15][16][17]. In the present case report, we could not find any statistical differences between changes in the gingival recession parameters measured by means of digital analysis or conventional clinical method.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Nevertheless, several more successful approaches were described in the literature in terms of digital evaluation of gingival recession [16]. Moreover, the digital approach used for the measurements of gingival recession was found to be more reproducible and valid compared to the conventional clinical examination [14][15][16][17]. In the present case report, we could not find any statistical differences between changes in the gingival recession parameters measured by means of digital analysis or conventional clinical method.…”
Section: Discussioncontrasting
confidence: 42%
“…On the other hand, several previous studies have demonstrated the advantages of using digital intraoral scanning approach in terms of recession level registration, while pointing to the proper validity, reliability, and accuracy of such method [14][15][16][17]. Ongoing digitalization in dentistry is supported by the unique possibilities of innovative available techniques and equipment, which further could be implemented in various clinical settings and for different specific objectives.…”
Section: Introductionmentioning
confidence: 99%
“…При цьому серед захворювань пародонту значного поширення набула рецесія ясен, або гінгівальна рецесія, що являє собою незапальну апікальну міграцію ясеневого краю від його фізіологічного розташування [1,5]. Зважаючи на те, що оголення кореня зуба, яке відбувається внаслідок ясеневого зміщення, стає не лише естетичною вадою, але й викликає у пацієнтів дентальну гіперчутливість, пришийковий карієс та некаріозні ураження, і навіть становить реальну небезпеку втрати зуба, вивчення причин й особли-востей розвитку рецесії ясен, її вчасного виявлення є надзвичайно важливим й актуальним [4,10,11,14,33,36].…”
unclassified